GAMBARAN PENGETAHUAN, SIKAP DAN TINDAKAN SISWA DALAM PEMILIHAN SAMPAH DI SD MUHAMMADIYAH 3 KOTA PADANGSIDIMPUAN - Nasution, Nurul Hidayah; Siregar, Yuli Arisyah; Jufri, Soleman; Harahap, Dewani; Habibah, Nursalmah; Batubara, Adli Zil Ikrom; Mapilinda, Via Nesa; Harahap, Rosmawarni (Universitas Aufa Royhan, 2025)
One of the developing countries that produces the most waste is Indonesia. The waste problem in Indonesia is now a serious threat if not handled properly. Waste reduction efforts aim to ensure that all elements of society, including the government, the business sector, and the general public, can implement waste reduction measures. Elementary schools are the most important educational institutions for teaching students how to behave appropriately in accordance with the norms of the environment in which they live. The purpose of this study was to determine the knowledge, attitudes, and actions of students in waste sorting at SD Muhammadiyah 3 Kota Padangsidimpuan. This was a quantitative study with a descriptive design. The population and sample consisted of 30 fifth-grade elementary school students. The sampling technique used was total sampling. The research instrument was a questionnaire. The questionnaire consisted of four parts, namely respondent identity, knowledge questionnaire, attitudes, and actions in waste sorting. Data processing was carried out through editing, coding, and entry. Data analysis used univariate analysis. The results of this study showed that the majority of elementary school students had sufficient knowledge, namely 18 students (60%). The attitudes of elementary school students were positive, namely 26 students (86.7%). The actions of elementary school students were to sort waste, with 25 students (83.3%) doing so. It is recommended that schools improve their environmental education programs to be more interactive, such as through hands-on waste sorting practices, school waste banks, and classroom cleanliness competitions so that students become accustomed to sorting waste.